La motricidad gruesa para el desarrollo integral de los niños de educación inicial en el sector rural, cantón Riobamba - Lliquin Chulli, Jacqueline Sofía (2024)
The present research work entitled; "The Gross Motor Skills for the Integral Development of Children in Early Education in the Rural Sector Riobamba City" has as its main objective to determine the importance of gross motor skills for the integral development of children in early education in the rural sector, since the child from early childhood must develop skills such as gross motor skills, this implies that the child performs general movements using only the large parts of his body, and also develops skills such as coordination, balance, body awareness and spatial orientation, which will help the child to have an integral development and perform positively throughout his life. The type of research carried out in the project is field and bibliographic since information is selected from articles, magazines, and repositories, thus obtaining reliable information; for data collection, a test was used to measure motor skills, which evaluates children's gross motor skills in early education. After obtaining the results through data tabulation, it is concluded that the children have well-developed gross motor skills. However, they show deficiencies in coordination and laterality.